3D printed poly(lactic acid) scaffolds modified with chitosan and hydroxyapatite for bone repair applications. (December 2020) - Nazeer, Muhammad Anwaar; Onder, Ozgun Can; Sevgili, Ilkem; Yilgor, Emel; Kavakli, Ibrahim Halil; Yilgor, Iskender
Graphical abstract: Highlights: 3D printed PLA scaffolds were prepared through fused deposition modelling. PLA surface was functionalized using chitosan and hydroxyapatite. Composite scaffolds were characterized by FTIR, SEM, XRD and other techniques. Wetting behavior of PLA surface was improved after chitosan and hydroxyapatite incorporation. In vitro cell viability analysis showed improved proliferation of bone cells. Abstract: 3D printed poly(lactic acid) (PLA) scaffolds surface modified with chitosan (CS) and hydroxyapatite (HA) to produce a novel bioactive composite scaffold is reported. Excellent mechanical properties of PLA, the bioactivity of CS, and osteogenic characteristics of HA are combined to fabricate composite scaffolds using a simple desktop 3D printer. Scaffolds were characterized through attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, X-ray diffraction (XRD) and water contact angle measurements before and after modification. Formic acid was used as a solvent to prepare stable CS/HA dispersions and was found to be a suitable solvent for producing PLA/CS/HA composites. Surface properties of modified scaffolds were superior in terms of hydrophilicity and bioactivity, which resulted in enhanced attachment and proliferation of human osteosarcoma cells in vitro compared to the unmodified PLA scaffolds.